2011
DOI: 10.1292/jvms.10-0154
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study in 21 Shiba Dogs with Chronic Enteropathy

Abstract: ABSTRACT. We retrospectively studied the clinical and laboratory features and outcomes of chronic enteropathy in Shiba dogs. Among 99 dogs with chronic enteropathy, 21 Shiba dogs (21%) were included in the study (odds ratio, 7.14). No significant differences were seen in signalment, clinical signs, symptoms or laboratory profiles between the Shiba and non-Shiba groups. Severe histopathological lesions in the duodenum were a common finding in the Shiba group. The median overall duration of survival in the Shiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
3
16
2
Order By: Relevance
“…In a previous study on Shiba dogs with CE, the median age was 4.9 years [6], which was almost comparable to the ages reported in other retrospective studies of dogs with IBD and CE [10-12]. Similarly, in our study, the median age of the Ls group was 5 years (mean 5.2).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In a previous study on Shiba dogs with CE, the median age was 4.9 years [6], which was almost comparable to the ages reported in other retrospective studies of dogs with IBD and CE [10-12]. Similarly, in our study, the median age of the Ls group was 5 years (mean 5.2).…”
Section: Discussionsupporting
confidence: 89%
“…There were no previous reports assessing the CIBDAI in Shiba dogs with CE; however, there was one report that found anorexia and a decrease in activity were more likely to be present in the non-survivor than in the survivor Shiba group [6]. Another study found that anorexia and severe weight loss in dogs with LPE, including many Shiba dogs, were significantly more evident in non-survivors than in survivors, and suggested that anorexia could be a risk factor of poor outcome [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enteritis might have been caused by a gastrointestinal disease other than parasitic infection. Shiba dogs with chronic enteropathy have a poor prognosis [14,15]. Furthermore, a neoplastic disease, such as lymphoma, might also have been a cause of death.…”
mentioning
confidence: 99%